Identifying the pleasant sounds in the city's public parks environment (Case study: Mellat riverside park, Urmia) - Ghalehteimouri, Kamran Jafarpour; Shamsoddini, Ali; Bayramzadeh, Nima; Mousavi, Mir Najaf (Street Art & Urban Creativity, 2023)
Noise pollution is a prevalent issue in contemporary public spaces, leading to discomfort and mental distress in individuals. This study aims to improve the quality of soundscape in urban public spaces and enhance the comfort and well-being of citizens. Using a mixed-methods approach, including literature review, field observations, questionnaires, and interviews, the research was conducted at Mellat Park in Urmia, Iran. The sample consisted of 170 randomly selected park visitors, who were surveyed to gather data. The findings indicate that the majority of visitors prefer the use of music in public spaces but emphasize the importance of a balanced audio environment. The results further reveal that natural sounds were found to be the most preferred type of sound, as they provide a sense of leisure, relaxation, and calmness. This study highlights the significance of creating a harmonious soundscape in public spaces to improve the overall experience and comfort of citizens. The low level of Sig, Water sound, Car sound, Speakers sounds, Types of treble sounds, and Types of bass sounds differs significantly from the average level due to the positive upper and lower 95% confidence in the water sound, this value is also higher than the average. Because of the negative upper and lower 95% confidence levels in the car sound, speakers sounds, types of treble sounds, and types of bass sounds, this value is lower than the average level.